Should we offer deep brain stimulation to Parkinson’s disease patients with GBA mutations? - Artusi, Carlo Alberto; Lopiano, Leonardo (Frontiers in Neurology, 2023)
Parkinson’s disease (PD) patients who are carriers of glucosylceramidase β1 (GBA1) gene mutations typically show an earlier age at onset and a more aggressive disease course, with a higher burden of neuropsychological issues. The use of Deep Brain Stimulation (DBS) in PD patients with disabling motor fluctuations and absence of dementia is a widespread therapeutic option, often with good results in terms of improvement in activities of daily living and quality of life. Although all PD patients, when fulfilling the common selection criteria for DBS, can profit from this intervention, some studies have raised attention toward the fact that PD carriers of GBA1 variants may have a worse DBS outcome, primarily due to an accelerated progression of cognitive decline. In this viewpoint, we summarize the current literature evidence, highlighting the knowledge gaps and proposing suggestions for further research efforts as well as for clinical practice in this timeframe of uncertainty related to the PD candidates for DBS carriers of GBA1 variants.